2019
DOI: 10.3847/1538-4357/ab1593
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Mass Segregation Effect of X-Ray Sources in Globular Clusters: The Case of 47 Tucanae

Abstract: Using archival Chandra observations with a total exposure of 510 ks, we present an updated catalog of point sources for Globular Cluster 47 Tucanae. Our study covers an area of ∼ 176.7 arcmin 2 (i.e., with R 7.5 ′ ) with 537 X-ray sources. We show that the surface density distribution of X-ray sources in 47 Tuc is highly peaked in cluster center, rapidly decreases at intermediate radii, and finally rises again at larger radii, with two distribution dips at R ∼ 100 ′′ and R ∼ 170 ′′ for the faint (L X 5.0 × 10 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(61 citation statements)
references
References 61 publications
7
53
1
Order By: Relevance
“…From Figure-1, it can be seen that the X-ray sources are uniformly dispersed in the Chandra FoV of ω Cen, and few bright sources (F p 1.0 × 10 −6 photon cm −2 s −1 ) are located within the cluster core. These features are different from other GCs studied in this series of work (i.e., 47 Tuc, Terzan 5 and M 28; Cheng et al 2019aCheng et al ,b, 2020, where the bright X-ray sources are mainly concentrated in the cluster center and significant radial distribution dips, a signature of mass segregation, can be observed in the F p − R diagram. To explore the mass segregation of X-ray sources in ω Cen, we study the radial surface density profile of X-ray sources in .…”
Section: Analysis: Source Raidal Distribution and Binary Burning Processescontrasting
confidence: 83%
See 3 more Smart Citations
“…From Figure-1, it can be seen that the X-ray sources are uniformly dispersed in the Chandra FoV of ω Cen, and few bright sources (F p 1.0 × 10 −6 photon cm −2 s −1 ) are located within the cluster core. These features are different from other GCs studied in this series of work (i.e., 47 Tuc, Terzan 5 and M 28; Cheng et al 2019aCheng et al ,b, 2020, where the bright X-ray sources are mainly concentrated in the cluster center and significant radial distribution dips, a signature of mass segregation, can be observed in the F p − R diagram. To explore the mass segregation of X-ray sources in ω Cen, we study the radial surface density profile of X-ray sources in .…”
Section: Analysis: Source Raidal Distribution and Binary Burning Processescontrasting
confidence: 83%
“…The AE binomial no-source probability (P B ) parameter was adopted to evaluate the significance of X-ray sources. As demonstrated in the case of 47 Tucanae, we set a more stringent threshold value of P B 1 × 10 −3 for validated X-ray sources, which was proved to be helpful in optimizing the source completeness and reliability (Cheng et al 2019a). On the other hand, the threshold value of P B also offers us a criterion to calculate the limiting detection sensitivity across the FoV of ω Cen.…”
Section: Sources Detection and Sensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, spectra of such CVs could be relatively easy to obtain, since crowding should not be a big problem in the outer parts. With respect to observations, Cheng et al (2019a [164]; 2019b [165]; 2020 [166]) recently investigated the phenomenon of mass segregation in the GCs 47 Tuc, Terzan 5 and M28. These authors confirmed that there are some X-ray sources located outside the half-light radii and showed that the radial distribution of X-ray sources in these clusters is bimodal, with features similar to those found in the radial distribution of blue stragglers, they being modulated by mass segregation of primordial binaries.…”
Section: Simulations By Belloni Et Al (2019)mentioning
confidence: 99%